Interactive Learning Factory Demonstrator for high school students - Soraia Filipa Neves da Silva (2020)
Manufacturing is one of the key sectors within the European Union, whose technological development is used to guarantee Europe's future and evolution. In Portugal there is a need for technological evolution, since we are below average. Therefore, it is necessary that there is a level of educational investment in technological areas such as engineering. This investment must be made at the levels of education before students enter higher education, as it is important that young people have contact with this type of technology as early as possible. This contact will allow young people to gain a more positive and realistic perspective of the industrial sector, as well as to learn about various career opportunities related to this important sector. Consequently, interest in technological areas increases, which, consequently, increases the number of students in technological courses. Bearing these factors in mind, this dissertation aims at the development of a gamified website whose objective is to allow high school students to become familiar with some basic concepts about the industrial sector and the technologies involved, such as cyber-physical systems, robotics, optimization, artificial intelligence, among others. The goal is to use innovative methods and concepts to develop a demonstrator that is interactive, which will pique students interest. The objective of this dissertation is to develop the concept and pedagogical strategy for an "Interactive Learning Factories Demonstrator", where a gamified website will be used, it will be used to transmit to students concepts about cyber-medical systems. The "Interactive Learning Factory Demonstrator" will be used to motivate and increase the interest of young foreigners, with special emphasis on high school students (aged 15-18), for activities in the field of manufacturing. Attracting young students to the manufacturing field is a current need. The creation of innovative and creative methodologies and technologies to demonstrate engineering concepts is an interesting field of research that can be applied to the manufacturing domain and later transferred to other engineering domains.